The Effectiveness of Kid Songs on Students’ Motivation in Learning Listening Comprehension - Jamil, Nurasyia; Jabu, Baso; Sakkir, Geminastiti (State University of Makassar, 2025)
The purpose of this research is to find out the effectiveness of kid songs on student motivation in learning listening comprehension. This research was conducted at SMPN 18 MAKASSAR The population in this study is class IX students. Researcher use a random cluster technique where they select 25 students from the class that has the highest number of students without certain criteria. This research uses the pre-experimental one group pretest posttest design method. The instruments used by researcher are listening tests and questionnaires. Do some treatment and at the end of the meeting it is done, back to the listening test. Based on the results of the average calculation, it is known that the use of Kid songs can improve their listening comprehension, where the posttest mean is greater than the mean pretest. Then the researcher concluded that the use of kid songs was effective to motivate students in learning listening comprehension. Students respond to the effectiveness of using kid songs in listening understanding quite positively. Their answers to the questionnaire were dominated by positive responses, they certainly had agreed thoughts about the effective use of kid songs in motivating students for their listening comprehension.Keywords: Kid songs, Listening Comprehension, Motivation